A Difficult Diagnosis: A Qualitative Study of the Daily Lives of Young Men Diagnosed with Ankylosing Spondylitis. (21st August 2016) - Primholdt, Nina; Primdahl, Jette; Hendricks, Oliver
Abstract: Objectives: The majority of patients with ankylosing spondylitis (AS) are young men, and there is limited knowledge about how these men live their everyday lives with the disease. The aim of the present study was to generate knowledge and an understanding of how this group of patients live from day to day, and how they meet the challenges they face in relation to their disease. Methods: The study was based on a qualitative research design and consisted of semi‐structured interviews with men diagnosed with AS. The men were recruited from a rheumatological hospital in Denmark. The study's theoretical framework was grounded in critical psychology, and the analysis was based on Kvale and Brinkmann's meaning condensation. Results: The five men interviewed were 21–37 years old. At the time of the interview, the participants had been diagnosed with AS for an average of 2.6 years, with an average time from the onset of symptoms to diagnosis of 5.4 years. The analysis resulted in the following three themes: 'Daily living and psychological reactions', 'A difficult diagnosis' and 'Working life and identity'. Conclusions: It took a long time to make the correct diagnosis, and the period before diagnosis was characterized by great uncertainty regarding the men's prospects. In addition, physical limitations, depression and stress had an inhibitory impact on the men's everyday lives. It was important for the men to stay in the work force and to be able to change their career direction, which was necessary for the men whose jobs involved hard physical work. Copyright © 2016 John Wiley & Sons, Ltd.